An Analysis Meaning of the Verb ‘to See’ in Banjarese Language: A Natural Semantic Metalanguage Studies - Fahmi, Iftitah Amalia Mutiara; Kepirianto, Catur; Nurhayati, Nurhayati (Humanis, 2024)
The aim of this study is to explicate and describe the verb malihat, which is synonymous with the verb 'to see' in the English language. The qualitative method was used to explain the explication of verbs ‘to see' in the Banjarese Language. The primary data were obtained from interviews with Banjarese native speakers. The secondary data were from written sources to assess the validity of the data. The data was analyzed using the Natural Semantic Metalanguage (NSM) theory by Anna Wierzbicka. The results of the study found nine types of the verb malihat in the Banjarese language. There are meitihi, tebincalak, menjanaki, meawasi, manonton, maintip,   mailangi,  mancilingi or mancelengi,   and manyirit. Furthermore, those verbs are polysemous into four categories: seeing and feeling, seeing and knowing, seeing and saying, and seeing and doing something.